Nonlinear Performances of Three-Phase Flux Reversal Motor Employing Modular Rotor for Multi Speed Air Blower - Rosnei, Muhammad Hazieq Ahnaf; Jenal, Mahyuzie (Evolution in Electrical and Electronic Engineering, 2024)
This project tackles the limitations of current air blower systems, which rely on inefficient single-phase power for variable speeds. It focuses objectively on a new design using a three-phase flux reversal motor (FRM) with a modular rotor to achieve efficient multi-speed operation and reduce energy consumption. The project will compare the performance of FRMs with different rotor designs (12 vs 24 slots) to find the most optimal solution. JMAG software was used, with JMAG Geometry Editor for creating motor parts (stators, rotors, etc.) and JMAG Designer for analysis. The Geometry Editor allows for precise sketching with various tools. Once the motor is created, JMAG Designer is used to define materials, conditions, and run simulations. This includes defining the electric circuit (coils) and mesh settings. Finally, the simulation is run to generate results that show motor performance. This study tested the flux linkage of the motor's coils and how it changes with rotation. Then looked at the motor's capabilities under load by increasing the current density. This analysis showed that torque and power increased with current density, while speed decreased. Finally, this study looked at iron and copper losses in the motor at various speeds and found that design 1 offered better overall efficiency. The design (12 coils, 24 coils) was analyzed using JMAG software and showed good performance, especially in efficiency (93%) and power handling. However, the torque is modest (5 Nm). For future work, this study recommends 3D finite element analysis, genetic algorithm optimization, and magnetic field analysis to improve the design further